(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND) is an integral part of the management of patients with metastatic non-seminoma and residual masses >1 cm after chemotherapy. AIMS: To assess perioperative complications and oncological outcomes at two major referral centres in Switzerland. METHODS: This was a retrospective chart review of 136 patients with non-seminoma who underwent PC-RPLND between 2010 and 2020 at the university hospitals of Bern and Zürich. Patient, treatment and tumour characteristics as well as the types and frequencies of intra- and postoperative complications were registered and compared using the chi-square test. Oncological outcomes consisted of the time and location of relapses as well as progression-free and overall survival, which were compared using the log-rank test. RESULTS: Overall, 70 patients from Bern and 66 patients from Zürich were included; 5 patients had a previous retroperitoneal lymph node dissection (RPLND) (2 Bern, 3 Zürich). Vascular injuries were the most frequent intraoperative complication, occurring in 27/136 (19.9%) patients. Postoperative complications were observed in 42/136 (30.9%) patients, ileus being the most common. Perioperative mortality was 2.2%. A retroperitoneal mass ≥50 mm was significantly associated with intraoperative complications (p = 0.004) and increased resource demands (p = 0.021). Postoperative morbidity was higher according to age at post-chemotherapy retroperitoneal lymph node dissection ≥40 years (p = 0.028) and retroperitoneal mass ≥20 mm (p = 0.005). The median follow-up time was 37 months (interquartile range [IQR] 18–64 months). The median progression-free survival at 5 years was 76% (95% confidence interval [CI]: 64–85%) in Bern and 69% (95% CI: 54–80%) in Zürich (p = 0.464). The median overall survival at 5 years was 88% (95% CI: 76–94%) in Bern and 77% (95% CI: 60–87%) in Zürich (p = 0.335). Patients with progressive disease or a tumour marker increase before retroperitoneal lymph node dissection had significantly inferior progression-free and overall survival compared to non-progressing patients. The presence of teratoma in resected specimens did not confer inferior survival probabilities compared to necrosis only, whereas the presence of vital undifferentiated tumour conferred inferior progression-free and overall survival. Patients with a previous retroperitoneal lymph node dissection and patients operated for late relapses >2 years after chemotherapy also had significantly inferior progression-free and overall survival. CONCLUSIONS: We found a relevant rate of severe perioperative complications at PC-RPLND at even experienced high-volume centres. The oncological outcomes at two major university urological centres in Switzerland were similar and determined by preoperative risk factors and intraoperative histology.